Technology of oppression : preserving freedom and dignity in an age of mass, warrantless surveillance - Cohen, Elliot D.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
In the aftermath of the Edward Snowden leaks, the Obama administration has been hard pressed to yield to greater transparency and openness to constructive change. This book provides a catalyst toward greater transparency, increased public awareness of the urgent need for constructive change, and the insight into what such change would require.
Keywords: Science; Science; Science, general